Asian-driven resource booms in Africa: Rethinking the impacts on development - Breisinger, Clemens; Thurlow, James (International Food Policy Research Institute, 2008)
Today's resource boom in Africa, driven by Asian economic growth, offers new opportunities for resource-rich African countries. Contrary to the experience of previous booms, however, most mining profits now accrue to foreign companies, leaving little room for governments to use revenues for pro-poor investments or to mitigate adverse distributional impacts. Taking Zambia as a case study, this paper shows that despite privatization, Dutch disease remains a valid concern and may hamper economic diversification, worsen income distribution, and undermine poverty reduction strategies. Mining royalties must, therefore, be increased and used to finance growth-inducing investments that encourage pro-poor economic diversification, else many African countries will remain caught in a resource trap.